Peran Kamus Besar Bahasa Indonesia (KBBI) dalam Peningkatan Kualitas Berbahasa dalam Pendidikan - Wisnu Nurjaman; Desta Naufal Pandhya; Gilbran Shauma Aldebaran; Risyad Ben Buzzardy (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Language is a communication tool used by humans to convey thoughts, feelings and ideas. In the world of education, use of good language can help students to understand the material easily. This study aims to determine the role of KBBI in influencing the improvement of students language quality. The research method used is descriptive qualitative, this research was conducted 36 respondents of high school students and students who are undergraduate education. The results show that although many were initially unfamiliar with KBBI, academic needs encourage them to use it, usually they access the KBBI through applications and websites. KBBI helps in improving language understanding, enriching vocabulary and can develop good and correct language skills. KBBI should be introduced early in the curriculum to cultivate literacy and improve language qualitu.